2015
DOI: 10.1111/jopr.12400
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Year Outcome of Fixed Partial Rehabilitations Supported by Implants Inserted with Flap or Flapless Surgical Techniques

Abstract: Partial edentulism rehabilitation through immediate provisionalization fixed prosthesis supported by dental implants inserted through flap or flapless surgical techniques in areas of predominantly soft bone was viable at 3 years of follow-up. The limitations and risks of the "free-hand" method in flapless surgery should be considered when planning implant-supported fixed prosthetic reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Few studies have reported comparable outcome with both the techniques,[ 14 , 15 , 26 - 28 , 33 , 40 - 44 ] while few reported that flapless surgery can affect the bone more than flap surgery. [ 12 , 45 ] Difference in the outcomes could be because of the difference in the operating protocol. Few studies have used tissue punch,[ 10 , 23 , 33 , 43 , 46 ] while others have performed drilling directly through the mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have reported comparable outcome with both the techniques,[ 14 , 15 , 26 - 28 , 33 , 40 - 44 ] while few reported that flapless surgery can affect the bone more than flap surgery. [ 12 , 45 ] Difference in the outcomes could be because of the difference in the operating protocol. Few studies have used tissue punch,[ 10 , 23 , 33 , 43 , 46 ] while others have performed drilling directly through the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Freehand flapless surgery could be considered less accurate and lead to greater bone loss as shown in the findings of one study by Maló et al . [ 45 ] The difference in the results could also be attributed to the implant location. Few studies have only included maxillary region,[ 15 , 41 , 42 ] while others included were not specific to the region.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of Job et al, 25 Malo et al, 49 and Tallarico et al, 58 all implants were loaded immediately and in four other studies 32,35,40,48 immediate implant loading was only done using flapless technique. In the other studies, implants were loaded following conventional protocols.…”
Section: Loading Protocolmentioning
confidence: 99%
“…However, the difference was not significant in eight studies. [28][29][30][31][32][33]52,53 In the studies of Malo et al, 49 and Pisoni et al, 51 marginal bone loss was higher in the flapless group, however Malo et al, 49 reported no statistical analysis for comparison between two groups and Pisoni et al 51 showed no significant difference between the two groups. In the RCTs by Bömicke et al 55 and Kumar et al 57 marginal bone loss was significantly lower in the flapless group.…”
Section: Alveolar Bone Lossmentioning
confidence: 99%
“…8 The circumferential supracrestal fiberotomy in flapless surgery may sacrifice more limited attached gingival tissue than does traditional open flap surgery. 9 In addition, the high costs of surgical guide manufacture and the demand for accuracy in laboratory production limits the clinical applications when considering patients' desires. 10 A variety of factors contributed to the success of implantation, although consensus cannot be reached on whether each factor leads to significant differences in results.…”
mentioning
confidence: 99%